SINONIMITAS DALAM AL-QUR’AN (Makna Lafadz ‘Alima dan ‘Arofa Perspektif al-Zamakhsyari) - M. AZHARI, AZHARI (el-Umdah, 2025)
This study examines the meaning of 'alima and 'arofa contained in the book of tafsir al-kasysysaf by al-Zamakhsyari, this study aims to provide new knowledge related to the meaning contained in the verses of 'alima and 'arofa. With regard to the meaning of 'alima and 'arofa which means knowing, is a trait that requires an object. So to know and understand it, linguistic analysis is needed. As an approach, the author uses thematic figures, namely, al-Zamakhsyari in the book of tafsir al-kasysysaf. In this research method using qualitative methods with the type of library research. Library research is a study in which all data are in the form of written materials such as books, journals, manuscripts and previous scientific research, which discusses lafadz 'alima and 'arofa in the book of tafsir al-kasysysaf by al-Zamakhsyari with descriptive analysis techniques. The results of this study indicate that the interpretation of al-Zamakhsyari in explaining the lafadz 'alima and 'arofa has similarities and differences. The similarities of the two are both "knowing" while the difference is that the lafadz 'alima in the text of the Qur'an is usually attributed to Allah SWT which is interpreted as proof that Allah SWT knows everything both before and after, and when the lafadz 'alima is attributed to humans, the meaning of knowledge must have an intermediary to be able to know it such as miracles and other wonders, then they will know. While lafadz 'arofa in the text of the Qur'an is always attributed specifically to humans, so that they know and understand, there is nothing higher and superior to human knowledge when it is in the side of Allah SWT.